DUTIES OF ACADEMICIANS TO THE UNIVERSITY AND HIS WORKING HOURS OF AN EVALUATION OF LEGISLATION AND CASE-LAW - Işık, Ensar (Cahit AYDEMİR, 2024)
Universities have problems related to education and scientific research, as well as legal and administrative problems. The services provided by state and foundation universities are considered public services and academicians are considered public officials. This situation sometimes causes academics to be evaluated like other public officials. However, due to scientific necessities and academic freedom, academics cannot be evaluated like other public officials. In order to prevent the problems experienced, legislation and practice need to be changed in terms of scientific necessity and academic freedom.

Üniversitelerin eğitim- öğretim ve bilimsel araştırmalarla ilgili sorunları olduğu gibi hukuki ve idari sorunları da vardır. Devlet ve vakıf üniversitelerinin sunduğu hizmet kamu hizmeti ve akademisyenler de kamu görevlisi sayılmaktadır. Bu durum bazen akademisyenlerin diğer kamu görevlileri gibi değerlendirilmesine neden olmaktadır. Ancak bilimsel gereklilikler ve akademik özgürlük gereği, akademisyenler diğer kamu görevlileri gibi değerlendirilemez. Yaşanan bu sorunların önüne geçilebilmesi için mevzuatın ve uygulamanın bilimsel gereklilikler ve akademik özgürlük açısından değiştirilmesi gerekmektedir.
AKADEMİSYENLERİN ÜNİVERSİTEYE KARŞI GÖREVLERİ VE MESAİ SAATLERİ HAKKINDA MEVZUAT VE İÇTİHAT BAKIMINDAN BİR DEĞERLENDİRME
Keywords: Law in Context (Other); Hukuk (Diğer)